A Study on Customer Satisfaction for Cakes of Monginis & TGB in Ahmedabad city - Bhoomika Gohel; Vyom Yadav; Jignesh Vidani (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2024)
This study delves into the competitive landscape of the cake market in Ahmedabad, focusing on the customer satisfaction levels for two prominent bakeries, Monginis and TGB. Through a comprehensive analysis of industry trends, market dynamics, and consumer preferences, the research aims to provide insights into factors influencing brand choice and overall satisfaction. Key findings indicate that while Monginis and TGB hold relatively equal market shares, Monginis enjoys a slight edge in terms of overall customer satisfaction, particularly regarding cake quality and meeting taste expectations. However, both bakeries have their loyal customer bases, highlighting the importance of understanding specific drivers of preference. The study underscores the significance of ongoing customer satisfaction research and tailored offerings to adapt to evolving consumer preferences and maintain a competitive edge in the dynamic cake market of Ahmedabad. Furthermore, the high interest in follow-up interviews suggests an opportunity for deeper insights and refinement of strategies to capture a larger market share. Objective: This study aims to assess and compare customer satisfaction levels for cakes offered by Monginis and Theobroma (TGB) in Ahmedabad City, Gujarat, India. Analysis: Quantitative data will be analyzed using statistical methods to compare satisfaction levels between Monginis and TGB across different factors. Qualitative data will be analyzed using thematic analysis to identify key themes and patterns in customer experiences. Expected Outcomes: The study is expected to provide insights into the relative strengths and weaknesses of Monginis and TGB in terms of customer satisfaction for cakes. This information can be valuable for both brands in developing strategies to improve customer satisfaction and gain a competitive edge in the Ahmedabad cake market.